GAMBARAN TINGKAT PENGETAHUAN MASYARAKAT TENTANG KEGAWATDARURATAN DI KAWASAN PARIWISATA - I Made Suindrayasa; Meril Valentine Manangkot (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2020)
Emergency conditions are conditions that occur unexpectedly, anytime, anywhere and require immediate treatment. Knowledge of day-to-day emergencies is needed to support the tourism industry. With increased knowledge about emergencies it will provide a sense of security and comfort for tourists. This study aims to describe people's knowledge about emergencies in the tourism area. This research is a descriptive study involving 95 respondents. The results of this study indicate that the level of public knowledge about emergencies in tourist areas is in the moderate category of 56.84%. The conclusion of this study is the level of public knowledge about emergencies still needs to be improved. Suggestions from this research are the need for efforts to increase public knowledge about emergencies to support the tourism industry. Keywords: knowledge, emergency, tourism